2014
DOI: 10.1097/inf.0000000000000375
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Status and Waning of Measles Antibody Concentrations after Measles Immunization

Abstract: Background Asthmatics have increased risks of common and serious microbial infections including vaccine preventable diseases. Little is known about whether asthma influences waning of humoral immunity. We assessed whether asthma status influences waning of anti-measles virus antibody concentrations over time. Methods The study utilized a cross-sectional study cohort of healthy children who had been immunized with one-dose of MMR-II at age approximately 15 months. Between 5 and 12 years of age, measles vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…1 Recently, we reported that children with clinical asthma and those with an immunogenetic predisposition to asthma (develop asthma later) have a more rapid waning of measles vaccine virus-specific immunoglobulin G levels over time than those without asthma (a decrement of Ϫ0.114 unit per year in children with asthma versus Ϫ0.046 unit per year in children without asthma; p value for trend ϭ 0.01). 4 Because a history of asthma ever is associated with the risk of breakthrough varicella infection, our study results might be consistent with these study findings. We postulated that asthma may affect the kinetics of vaccine-induced memory B cells or long-lived plasma cells.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…1 Recently, we reported that children with clinical asthma and those with an immunogenetic predisposition to asthma (develop asthma later) have a more rapid waning of measles vaccine virus-specific immunoglobulin G levels over time than those without asthma (a decrement of Ϫ0.114 unit per year in children with asthma versus Ϫ0.046 unit per year in children without asthma; p value for trend ϭ 0.01). 4 Because a history of asthma ever is associated with the risk of breakthrough varicella infection, our study results might be consistent with these study findings. We postulated that asthma may affect the kinetics of vaccine-induced memory B cells or long-lived plasma cells.…”
Section: Discussionsupporting
confidence: 83%
“…These results indicated that children with an immunogenetic predisposition to asthma may still have a potential risk for breakthrough varicella infection because they already have airway, clinical, and immunologic features of asthma before the development of clinical asthma. 4,18,19 There is evidence that the effect of atopic conditions on the risk of microbial infections or immune dysfunction might begin before the onset of clinical asthma. 19 -21 These findings may be consistent with the notion that some phenotypic features of asthma (e.g., poor lung function) begin before the development of clinical asthma in children (even during newborn period) (i.e., the "hypothesis of early programming of asthma").…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Both innate and adaptive immune dysfunctions associated with clinical asthma and immunogenic predisposition to asthma might play a role. One noteworthy study showed a more rapid waning of humoral immunity (antimeasles immunoglobulin G levels) over time in children with asthma than in children without asthma, 38 which potentially indicates that asthma might affect kinetics or functions of B cells over time in a way that makes the host susceptible to vaccineinduced microbial infections. 10 Given that cell-mediated immunity (CMI) is known to decline with age as part of immunosenescence and that decreased CMI is associated with reactivation of varicella zoster virus, our study results might indicate that asthma affects the waning of CMI in addition to the reported impaired innate immunity.…”
Section: Discussionmentioning
confidence: 99%